2004
DOI: 10.1017/s0265021504008117
|View full text |Cite
|
Sign up to set email alerts
|

Is intraperitoneal levobupivacaine with epinephrine useful for analgesia following laparoscopic cholecystectomy? A randomized controlled trial

Abstract: Intraperitoneal administration of levobupivacaine with epinephrine is associated with modest analgesia following laparoscopic cholecystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…13 In an effort to reduce the post-LC-related pain, several randomized clinical trials examined various analgesic modalities including NSAIDS, opioid, wound infiltration, and intraperitoneal analgesia with local anesthetics. 4,14,15 Unfortunately the outcome is inconclusive. Lee et al 16 failed to demonstrate effective treatment of shoulder tip pain with both incisional and intraabdominal local anesthetic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…13 In an effort to reduce the post-LC-related pain, several randomized clinical trials examined various analgesic modalities including NSAIDS, opioid, wound infiltration, and intraperitoneal analgesia with local anesthetics. 4,14,15 Unfortunately the outcome is inconclusive. Lee et al 16 failed to demonstrate effective treatment of shoulder tip pain with both incisional and intraabdominal local anesthetic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reported incidence of PLSP was 63% after laparoscopic cholecystectomy 6, 66% after laparoscopic adjustable gastric band surgery 7, 65.5% after laparoscopic appendectomy 8 and 83% after gynecological laparoscopic surgeries 5. For improving the postoperative quality of life (QOL) for these patients, various techniques, including low-pressure insufflation, no CO 2 insufflation, preemptive diaphragmatic local anesthetic irrigation and regional anesthesia to peritoneal surfaces, have been developed to reduce the PLSP 9-13. Unfortunately, the effectiveness of these techniques was quite varied and even conflicting 7.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Pain after laparoscopic cholecystectomy is affect by several factors including patient demographics, nature of underlying disease, surgical factors, volume of residual gas, type of gas used for pneumoperitoneum, and the pressure created by the pneumoperitoneum. [1318] A number of techniques have been described for reducing postlaparoscopy pain including: Preincisional infiltration and intraperitoneal instillation of levobupivacaine 0.25%;[19] intraperitoneal ropivacaine and a gas drain;[20] intraperitoneal levobupivacaine with epinephrine;[21] intraperitoneal application of bupivacaine plus morphine;[22] preincisional injection of bupivacaine;[23] pre-emptive intraperitoneal injection of ropivacaine;[24] and intraperitoneal lidocaine combined with intravenous or intraperitoneal tenoxicam. [25] It is suggested that post-laparoscopic cholecystectomy pain is multifactorial and methods for short term analgesia cannot improve postoperative functions or shortened hospitalization.…”
Section: Discussionmentioning
confidence: 99%